2012
DOI: 10.1155/2012/196921
|View full text |Cite
|
Sign up to set email alerts
|

Aurones: A Promising Heterocyclic Scaffold for the Development of Potent Antileishmanial Agents

Abstract: A series of (Z)-2-benzylidenebenzofuran-3-(2H)-ones (aurones) bearing a variety of substituents on rings A and B were synthesized and evaluated for their antiparasitic activity against the intracellular amastigote form of Leishmania infantum and their cytotoxicity against human THP1-differentiated macrophages. In general, aurones bearing no substituents on ring A (compounds 4a–4f) exhibit higher toxicity than aurones with 4,6-dimethoxy substitution (compounds 4g–4l). Among the latter, two aurones possessing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
(42 reference statements)
1
36
0
Order By: Relevance
“…The thermodynamically more stable Z-isomer always prevails, which also has been supported by the calculation of heat of formations of both the isomers (Z and E) (Atta- Ur-Rahman et al, 2001;Dewar et al, 1985). The results indicated that the Z-isomers exhibited lower potential energy than E-isomers, which indicated higher stability than E-isomers (Roussaki et al, 2012). In this regard, the X-ray crystallographic data of the synthesized aurone 2b provided good evidence which showed that the molecular structure of this compound was sustained as a Zisomer (Fig.…”
Section: Synthesissupporting
confidence: 56%
See 2 more Smart Citations
“…The thermodynamically more stable Z-isomer always prevails, which also has been supported by the calculation of heat of formations of both the isomers (Z and E) (Atta- Ur-Rahman et al, 2001;Dewar et al, 1985). The results indicated that the Z-isomers exhibited lower potential energy than E-isomers, which indicated higher stability than E-isomers (Roussaki et al, 2012). In this regard, the X-ray crystallographic data of the synthesized aurone 2b provided good evidence which showed that the molecular structure of this compound was sustained as a Zisomer (Fig.…”
Section: Synthesissupporting
confidence: 56%
“…It has been reported that the position and electronic nature of the substituents on the B-ring contributed significant Med Chem Res cytotoxic effects in the aurone compounds against Leishmania infantum and human leukemia cancer cells THP1 (Roussaki et al, 2012). The compound 4 0 -methylaurone revealed a significant inhibition effect with IC 50 value of 8.5 lM, as compared to 4 0 -chloroaurone (IC 50 = 14.5 lM) on THP1 cells (Roussaki et al, 2012).…”
Section: Structure-activity Relationshipmentioning
confidence: 98%
See 1 more Smart Citation
“…Aurones, (Z)-2-benzylidenebenzofuran-3-(2H)-ones ( Figure 1c), constitute a less studied subclass of flavonoids although they are isosteres of flavones 5,6 . However, they have attracted attention with promising biological potential such as anti-microbial 7 , anti-cancer 8 , anti-leishmanial [9][10][11] , anti-histaminic 12 , antiinflammatory 13 , antioxidant 14 , insect anti-feedant 15 , herbicidal 16 , anti-HIV 17,18 , anti-HCV (hepatis C virus) 19,20 , anti-malarial 21,22 , ChE inhibitory 23,24 , MAO inhibitory 25 activities in the specified studies. The observed biological potential is thought to be due to the similarity of adenine of ATP and the flavonoids, consequently inhibition of the activity of ATP-dependent enzymes and proteins, which is essential for the function of enzymes and receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Culture plastic dishes and plates (96-well) were purchased from Becton Dickinson (Franklin Lakes, NJ, USA). [7], (2Z)-6-methoxy-2-(phenylmethylene)-3(2H)-benzofuranone [8], (2Z)-6-methoxy-2-[(4-methoxyphenyl)methylene]-3(2H)-benzofuranone [9], (2Z)-2-[(3,4-dimethoxyphenyl)methylene]-6-methoxy-3(2H)-benzofuranone [10] and (2Z)-2-[(4-bromophenyl)methylene]-6-methoxy-3(2H)-benzofuranone [11] were synthesized by the oxidative cyclization of 2'-hydroxychalcone derivatives, according to previous methods (13). Also, (2Z)-2-[(3,4-dimethoxyphenyl)methylene]-6-hydroxy-3(2H)-benzofuranone [12], (2Z)-2-[(4-fluorophenyl)methylene]-6-hydroxy-3(2H)-benzofuranone [13] [16] and (2Z)-2-[(3,4-dihydroxyphenyl)methylene]-6-hydroxy-3(2H)-benzofuranone [17] were synthesized by the condensation of 6-hydroxy-3(2H)-benzofuranone with selected benzaldehyde derivatives, according to previous methods (14).…”
Section: Methodsmentioning
confidence: 99%